When policy meets reality: the new 18-hour on-call shift policy and the Israeli anesthesia workforce crisis - Ariel Wimpfheimer; Charles Weissman; Shai Fein; Yehuda Ginosar; The Israel Anesthesiology Workforce Study Group (BMC, 2023)
Abstract Background The Israeli physician workforce faces multiple challenges. These include planned policies reducing physician on-call from 26 to 18 h and, from 2026, allowing only graduates of Ministry of Health approved foreign medical schools to take the Israeli licensing examination and an ongoing physician shortage (2019: Israel had 3.19 physicians/1000 persons vs. OECD average of 3.49 physicians/1000 persons). This study examines the potential impact of these planned policies on the Israeli anesthesiology workforce. Methods Surveys conducted among 34 public and private Israeli hospital anesthesiology department chairs collected data on their department's number of weekday on-call anesthesiologists and current shortage of anesthesiologists. A subsequent survey collected data on each anesthesiologist in the workforce, including the country where they studied medicine. Results Each weekday night there were 114 on-call anesthesiologists; 72 residents and 42 attendings. Using productive work coefficients, this translates to 104 resident and 51 attending anesthesiologists. Furthermore, 21 departments had existing anesthesia workforce shortages totaling 110 anesthesiologists. There were 873 anesthesiologists from non-OECD countries whose medical schools are not accredited by the World Federation for Medical Education, of whom 332 were residents (61.9% of residents). Only 20.1% of anesthesiology residents were Israeli medical school graduates. Conclusions Descriptive survey data assessed the immediate and long-term consequences for the healthcare system and anesthesiology workforce of two new Health Ministry policies. Implementing the 18-h policy will immediately remove from the daytime workforce 155 anesthesiologists and who will be unavailable to staff elective surgery operating rooms. This will compound the current national shortage of 110 anesthesiologists. It is unclear how to replace this shortfall since there are no surplus Israeli physicians and very few Israeli graduates choose anesthesiology as a specialty. This situation will be exacerbated after 2026 when graduates of certain foreign medical schools will be unable to enter the medical workforce, further reducing the pool of potential anesthesiology residents. Both policies were promulgated without adequate operational and budgetary planning or fiscal or workforce resources; implementation of the 18-h on-call policy has already been postponed. Therefore, new or updated policies must be accompanied by specific operational plans, budgetary allocations and funds for additional workforce.